Mechanistic Insights on Salicylic Acid Mediated Enhancement of Photosystem II Function in Oregano Seedlings Subjected to Moderate Drought Stress - Moustakas, Michael; Sperdouli, Ilektra; Moustaka, Julietta; Şaş, Begüm; İŞGÖREN, SUMRUNAZ; Morales, Fermin (MDPI, 2023)
Dramatic climate change has led to an increase in the intensity and frequency of drought episodes and, together with the high light conditions of the Mediterranean area, detrimentally influences crop production. Salicylic acid (SA) has been shown to supress phototoxicity, offering photosystem II (PSII) photoprotection. In the current study, we attempted to reveal the mechanism by which SA is improving PSII efficiency in oregano seedlings under moderate drought stress (MoDS). Foliar application of SA decreased chlorophyll content under normal growth conditions, but under MoDS increased chlorophyll content, compared to H2O-sprayed oregano seedlings. SA improved the PSII efficiency of oregano seedlings under normal growth conditions at high light (HL), and under MoDS, at both low light (LL) and HL. The mechanism by which, under normal growth conditions and HL, SA sprayed oregano seedlings compared to H2O-sprayed exhibited a more efficient PSII photochemistry, was the increased (17%) fraction of open PSII reaction centers (qp), and the increased (7%) efficiency of these open reaction centers (Fv '/Fm '), which resulted in an enhanced (24%) electron transport rate (ETR). SA application under MoDS, by modulating chlorophyll content, resulted in optimized antenna size and enhanced effective quantum yield of PSII photochemistry (phi(PSII)) under both LL (7%) and HL (25%), compared to non-SA-sprayed oregano seedlings. This increased effective quantum yield of PSII photochemistry (phi(PSII)) was due to the enhanced efficiency of the oxygen evolving complex (OEC), and the increased fraction of open PSII reaction centers (qp), which resulted in an increased electron transport rate (ETR) and a lower amount of singlet oxygen (O-1(2)) production with less excess excitation energy (EXC).
Keywords: Chlorophyll Fluorescence; Photosynthetic Efficiency; Light Reactions; Excess Excitation Energy; Origanum Vulgare; Reactive Oxygen Species; Photoinhibition; Photochemistry; Photoprotection